Characteristics of Legal Culture Study in Russian and Foreign Legal Literature - TERESHCHENKO, Elena Anatolevna; KOVALEV, Vladimir Viktorovich; BALAKIREVA, Lidiya Mikhailovna; SAVCHENKO, Elena Viktorovna; SOLOVTSOVA, Elena Anatolievna (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The article is dedicated to the research of problems of legal culture in national and foreign legal science. The particular difficulties were determined that arise on the way of jurists during the implementation of the specified task. The complexities were provoked by the relative non-development of the problems of legal culture in national legal science (the latter circumstance was due to the evident prevalence of the ideological postulates above the legal conscience). However, the complexities were overcome and by now the problems of legal culture took their position in the general range of legal sciences. The purpose of the present research is to consider and analyze the process of research of the problems of legal culture by national and foreign jurists, to determine the results of this process, and make the corresponding conclusions. Basing upon the previous accumulated experience and using the method of comparative analysis, performing the analogy and extrapolation between national and foreign researchers, on the one hand, and also between the studies of different periods, on the other hand, the authors of this research came to certain conclusions. The essence of the research is the significant results that were achieved in the field of studying the problems of legal culture. However, at the same time, basing upon that accumulated experience, it is necessary to perform the further research to solve the theoretical and practical problems as well.